An experimental study on the geochemical behavior of highly siderophile elements (HSE) and metalloids (As, Se, Sb, Te, Bi) in a mss-iss-pyrite system at 650 °C: A possible magmatic origin for Co-HSE-bearing pyrite and the role of metalloid-rich phases in the fractionation of HSE. (1st April 2016) - Cafagna, Fabio; Jugo, Pedro J.
Abstract: Pyrite, the most abundant sulfide in the Earth's crust, is an accessory mineral in several magmatic sulfide deposits. Although most pyrite is hydrothermal, previous experimental studies have shown that pyrite can also have a primary magmatic origin, by exsolving from monosulfide solid solution (mss) during cooling of a sulfide melt, if sulfur fugacity is sufficiently high. Pyrite from some localities has significant amounts of Co, and complex zonation in some low-melting-point chalcophile elements (LMCE), such as As, Se, Sb, Te, Bi (henceforth referred to as metalloids) and some platinum-group elements (PGE: Ru, Rh, Pd, Os, Ir, Pt). However, the origin of such pyrite and the causes of zonation are not clear. Because the distribution of some of these elements is heterogeneous and seems to be developed in concentric zones, the zonation has been interpreted to represent growth stages, some of them secondary and caused partly by hydrothermal fluids. Better constraints on the origin of Co-PGE-bearing pyrite could help unravel the geochemical processes affecting the sulfide assemblages in which it is found; thus, an experimental study was undertaken to characterize pyrite formation in magmatic sulfide environments and its relationship with metalloids and highly siderophile elements (HSE: PGE, Re, Au). Natural pyrrhotite, chalcopyrite, pentlandite and elemental S were mixed and doped with approximately 50 ppm of each HSE. A mixture of metalloids was added at 0.2 wt.% or 3 wt.% to aliquots of sulfide mixtures. Starting materials were sealed in evacuated silica tubes and fused at 1200 °C. The temperature was subsequently reduced to 750 °C (at 60 °C/h), then to 650 °C (at 0.5 °C/h) to produce relatively large euhedral pyrite crystals, then quenched. The experiments were analyzed using reflected light, SEM, EPMA and LA-ICP-MS. Experimental products contained euhedral pyrite, mss, intermediate solid solution (iss) and metalloid-rich phases, interpreted as quench product of an immiscible metalloid-rich liquid. The results show that Co-Ni-HSE-bearing pyrite with complex zonation in Ru, Rh, Os, Ir, and Pt can form by a subsolidus reaction involving both mss and iss, and does not require secondary (e.g. hydrothermal) processes. Because such pyrite results from the cooling of a sulfide melt (after mss and iss) it can be described as magmatic. Among the HSE, Ru, Rh, Os, Re and Ir have identical zonation patterns in pyrite, Pt is also zoned but differently, and Au and Pd are essentially excluded. Previously documented natural HSE-bearing pyrite also display identical zonation patterns in Ru, Rh, Os and Ir. The complex zoning is likely preserved due to the extremely slow diffusion rates for those elements in pyrite. Thus, the presence of pyrite with similar characteristic in natural sulfide assemblages is consistent with a magmatic origin and does not require hydrothermal processes. The results also show that if a metalloid-rich liquid is present it will significantly sequester Au, Pd and Pt, but will not affect Ru, Rh, Os, Re and Ir. In the absence of metalloid-rich phases, Au partitions strongly into iss and Pd partitions preferentially into mss.